"The Black", space, and sexuality: Examining resistance in Selvon's The Lonely Londoners. (June 2017) - Herald, Patrick
This article argues that theoretical notions of resistance and agency prove inadequate for considering the complexities of the treatment of Sam Selvon's Trinidadian characters. Indeed, to proceed from a binary logic of resistance and oppression carries the danger of universalizing those seen as oppressed, and smoothing over important complications in the novel. The Lonely Londoners, written at a pivotal moment of imperial decline, offers a valuable perspective on the experience of colonial immigration to England (and the accompanying complications of race and sexuality it wrought) as well as theories of resistance. By drawing on the circumspection of recent theorists, this article goes beyond the sort of analysis which might impose a binary logic of resistance and oppression on the complex intersections of race and sexuality on display in the novel. More specifically, The Lonely Londoners can be seen as grappling with and critiquing individualism, one of liberalism's chief values; formally, the novel's title invokes a group yet the narrative itself spends the majority of its pages detailing the individual lives of its characters, individual lives which stand in tension with their shared group identity and their daily struggles in postwar London. This tension between individualism and community reveals key moments — such as one character's personification of the colour black — as being symptomatic of a complex field of identity categories that Selvon's novel engages with. I argue that these categories should indeed be interrogated alongside the novel's depictions of metropolitan geography; however, I suggest that such an analysis is best served by also treating a key concept that might be taken for granted with the same complexity and diligence: resistance.